1992
DOI: 10.1136/ard.51.6.743
|View full text |Cite
|
Sign up to set email alerts
|

Antikeratin antibodies: diagnostic and prognostic markers for early rheumatoid arthritis.

Abstract: Antibodies to the stratum corneum of rat oesophagus (antikeratin antibodies) were assayed by indirect immunofluorescence in a prospective study of patients with early rheumatoid arthritis (RA). At the beginning of the study, antikeratin antibodies of IgG class were detected in serum samples from 27/71 (38%) patients compared with 1/20 (5%) control patients with reactive arthritis, and 1/38 (3%) healthy blood donors. At the end of the two year foliow up, 27/67 (40%) patients with RA were positive for antikerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
34
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 21 publications
7
34
0
1
Order By: Relevance
“…However, there was no difference in AFA positivity between the patients with and without marginal erosion in our patient group. It was reported that the frequency of RF is increased in AKA or APF positive patients (Paimela et al, 1992). In this study, the frequency of RF positivity tended to be higher in AFA positive patients compared with AFA negative patients (89% versus 67%, P = 0.18).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…However, there was no difference in AFA positivity between the patients with and without marginal erosion in our patient group. It was reported that the frequency of RF is increased in AKA or APF positive patients (Paimela et al, 1992). In this study, the frequency of RF positivity tended to be higher in AFA positive patients compared with AFA negative patients (89% versus 67%, P = 0.18).…”
Section: Discussionsupporting
confidence: 48%
“…The reported prevalence of AFA was variable (12.0-67.9%) and in case of AKA, the Greek patients with RA had low positivity (16%) in spite of consistently high positivity (36-69%) in other ethnic groups. AKA and APF could be positive at subclinical stage of RA (Paimela et al,1992) and IgG AKA was found in 38% of RA patients whose disease duration is less than one year (Aho et al, 1993). AKA and APF were suggested to be early diagnostic markers of RA.…”
Section: Discussionmentioning
confidence: 99%
“…This is not due to poor specificity of the test, since several studies (11)(12)(13)(14), including our own (ref. 15 and unpublished observations), have demonstrated the high specificity of AKA for RA.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that AKA also occur in seronegative RA, although at lower frequency than in seropositive RA (11)(12)(13)(14)(15). Those studies used the sensitized sheep-cell agglutination test to detect RF.…”
Section: Discussionmentioning
confidence: 99%
“…AKA were found to be associated with more severe and/or active forms of RA [14.34], to be detected at early stages [34] and even to precede the clinical onset of the disease [35].…”
Section: Discussionmentioning
confidence: 99%